동북아 경제협력과 남북한 경협의 연계 - 전홍택; 이영섭 (동아시아 통합전략(Ⅲ): 협력의 심화·확대와 새로운 도전, 2012)
유럽연합의 성공적인 확대, 북미 자유무역협정의 체결과 이에 대응하는 아세안 자유무역지대의 출범 등 다양한 지역무역협정의 확산 속에서 한⋅중⋅일 3국을 중심으로 한 동아시아 경제통합체의 형성에 대한 기대감과 당위성이 커지고 있다. 이러한 국제통상환경의 변화 속에서 우리나라는 2010년 G20 정상회의를 성공적으로 개최하며 국제사회에서의 리더십을 격상시켜 왔는데, 지속적인 국제적 영향력 확대와 중재자 역할을 수행해 나가기 위해서는 세계경제의 역동성을 이끌어 갈 동아시아 지역에서의 통합을 위한 주도적인 리더십이 뒷받침되어야 한다. 본 연구는 이러한 세계경제의 지역주의화 추세 속에서 한국의 생존전략으로서 동아시아 지역통합전략을 수립하기 위해 수행되었다. 2010년부터 2012년까지 3개년에 걸쳐 진행된 동아시아 통합연구는 동아시아 통합 구상, 한⋅중⋅일 공동체 추진을 위한 분야별 협력방안, 동아시아 통합의 확대 및 심화 방안을 다루고 있다. 본 보고서는 동아시아 통합연구의 3차연도 보고서로서 동아시아 경제통합의 아세안으로의 확대 및 통합을 위한 협력의 제도화, 그리고 과거 동아시아 통합 논의에서 간과되었던 남북한 경제협력과 동아시아 지역주의의 파급효과와 대응 등을 다루고 있다. 먼저 제Ⅰ부에서는 경제, 삶의 질, 환경, 정치행정, 문화 등 5가지 대분류 영역으로 구성된 지표체계와 생산네트워크를 활용하여 동아시아 통합여건을 분석하고, 역내 생산네트워크 강화에 따른 생산성 증가와 동아시아 FTA의 경제적 효과를 분석하였다. 제Ⅱ부 ‘동아시아 경제통합의 확대와 심화’에서는 동아시아 경제통합에 대한 아세안의 시각과 동아시아 공동체 형성을 위한 현실적 실천전략으로서의 협력의 제도화 방향을 제시하였다. 제Ⅲ부에서는 지역주의 파급에 따른 세계경제의 시나리오와 이에 대응하는 한국의 전략적 선택, 동아시아 경제통합 과정을 활용한 남북한 경제협력 추진방안을 제시하고, 2010년부터 2012년까지 3개년에 걸쳐 진행된 동아시아 통합연구의 결과를 요약함과 동시에 향후 정책적 시사점을 제시하였다. 본 연구는 동아시아 지역통합에 대한 아세안의 시각과 역할, 통합 촉진을 위한 제도화 방안과 남북한 경협 이슈, 세계경제 시나리오에 대한 한국의 대응 등을 분석함으로써 동아시아 협력의 확대와 심화를 위한 실천방안을 제시하였다는 점에서 의의를 찾을 수 있다. Ⅰ. Purpose Korea’s housing market in the 2000s has seen a couple of ongoing structural changes rendering the market framework. First, as chronic shortage of supply has been somewhat solved (at least on a nationwide basis), the expectation for a rise in house prices resulting from the mismatch between supply and demand is projected to weaken. Second, urban population which soared between 1970 and 1999 (40%→80%) posted little change at around 81% since 2000. Additionally, the scheduled relocation of government offices outside the capital region will lead to slowing the pace of concentration of population and economic activities in the capital region. Third, as the market for housing finance and real estate development financing grew, the role of institutional finance has increased. Accordingly, financial inclusion has broadened to cover more marginal borrowers, but at the same time the need to manage system risks—loan volatility spreading to macroeconomy—in an appropriate manner has risen as well. Fourth, changes in demographic and social structure resulting from low birth rate, population aging and small family trends have demanded a change in the types of housing. In the past, most of the supplied apartments were targeting a household with four members, but in the future, rental and self-owning houses will offer more variety in formats and styles. Lastly, the global financial crisis that started in the US and Europe between 2007 and 2009 has served as an opportunity for Korea to look back on issues and policies as to real estate market stabilization and housing welfare for mediumand low-income classes. This study aims to outline implications that the global financial crisis has brought to Korea’s housing sector which is presently undergoing several structural changes, such as reduced shortage of house supply, expanded institutional housing finance and changing demographics and social structures, and then to seek for a new paradigm for housing policy. The final paper includes 16 theses under six chapters including the introductory chapter, and its key policy implications are discussed under three categories below.